2016
DOI: 10.1017/sjp.2016.65
|View full text |Cite
|
Sign up to set email alerts
|

The Posttraumatic Growth Inventory: Factor Structure and Invariance in a Sample of Breast Cancer Patients and in a Non-Clinical Sample

Abstract: The Posttraumatic Growth Inventory (PTGI) is frequently used to assess positive changes following a traumatic event. The aim of the study is to examine the factor structure and the latent mean invariance of PTGI. A sample of 205 (M age = 54.3, SD = 10.1) women diagnosed with breast cancer and 456 (M age = 34.9, SD = 12.5) adults who had experienced a range of adverse life events were recruited to complete the PTGI and a socio-demographic questionnaire. We use Confirmatory Factor Analysis (CFA) to test the fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…Likewise, the psoriatic patients from the second profile, who were high in all types of resources, also had a higher PTG than did the control group, but the other profiles of psoriatic patients did not differ within that positive phenomenon from the healthy controls. One study on cancer patients did note a higher PTG level when compared to a non-clinical sample ( Ramos et al, 2016 ), but this study was conducted in a variable-centered framework (i.e., it disregarded the existence of various subgroups of patients with different psychosocial characteristics and thus had various levels of growth). In summary, it seems that, among patients with a chronic illness, the PTG is higher compared to individuals who have experienced acute traumatic life events, but only when the perceived resources level is high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the psoriatic patients from the second profile, who were high in all types of resources, also had a higher PTG than did the control group, but the other profiles of psoriatic patients did not differ within that positive phenomenon from the healthy controls. One study on cancer patients did note a higher PTG level when compared to a non-clinical sample ( Ramos et al, 2016 ), but this study was conducted in a variable-centered framework (i.e., it disregarded the existence of various subgroups of patients with different psychosocial characteristics and thus had various levels of growth). In summary, it seems that, among patients with a chronic illness, the PTG is higher compared to individuals who have experienced acute traumatic life events, but only when the perceived resources level is high.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is not known whether PTG may be experienced differently across various physical illnesses, particularly among patients who are exposed to a real-life threat versus those dealing with chronic but non-life-threatening medical conditions ( Purc-Stephenson, 2014 ). Finally, it would be interesting to explore whether there are some discrepancies in the PTG outlook among patients who are struggling with illness-related trauma compared to non-clinical samples who are exposed to acute traumatic life events ( Ramos, Leal, Marôco, & Tedeschi, 2016 ). In our study, we compared two groups of patients—cancer and psoriatic patients—with a non-clinical sample of adults from the general population who had experienced various adverse life events.…”
mentioning
confidence: 99%
“…When referring to the organic growth happening in nature, our Pitaguary respondents often spoke of their aspiration to transform ‘just as nature does’. This transformation process has often been linked to the concept of PTG described in both clinical and non-clinical samples across the world 16 94–96. However, in contrast to the Swiss group, only the Brazilian respondents spontaneously used the term ‘growth’ in direct speech, which may lead to a critique of the universal applicability of this metaphorical concept.…”
Section: Discussionmentioning
confidence: 99%
“…The PTGI measures the perceived degree of positive life changes following a traumatic event, and it consists of five domains: Relating to Others, New Possibilities, Personal Strength, Spiritual Change, and Appreciation of Life. In Portuguese version (Silva et al, 2009), PTGI is comprised by four subscales, however, we will use the five sub-scales in accordance with original article and with Ramos and her colleagues (Ramos et al, 2016b). The 21 items are rated on a 6-point Likert scale, ranging from 0 ( I did not experience this change as a result of having breast cancer ) to 5 ( I experienced this change to a very great degree as a result of having breast cancer ).…”
Section: Methodsmentioning
confidence: 99%
“…The PTGI has shown excellent internal consistency for the total scale (α = 0.90), as well as for the subscales (Relating to Others: α = 0.85; New Possibilities: α = 0.84; Personal Strength: α = 0.72; Spiritual Change: α = 0.85; Appreciation of Life: α = 0.67) (Tedeschi and Calhoun, 1996). The PTGI has also shown good psychometric properties in breast cancer Portuguese samples (Silva et al, 2009; Ramos et al, 2016b). In this study, the PTGI showed excellent reliability for the total score (α = 0.92) and good reliability for the subscales, with the Cronbach’s alphas for the subscales Relating to Others (α = 0.86); New Possibilities (α = 0.83); Personal Strength (α = 0.75); Spiritual Change (α = 0.73); and Appreciation of Life (α = 0.69).…”
Section: Methodsmentioning
confidence: 99%